Transcriptome Profiling of Layer 5 Intratelencephalic Projection Neurons From the Mature Mouse Motor Cortex - Clare, Alison J.; Day, Robert C.; Empson, Ruth M.; Hughes, Stephanie M. (Frontiers in Molecular Neuroscience, 2018)
The mature cortex contains hugely diverse populations of pyramidal projection neurons, critical to normal forebrain circuits. In order to understand the healthy cortex it is essential to characterise this neuronal complexity. We recently demonstrated different identities for Fezf2-positive (Fezf2+ve) and Fezf2-negative (Fezf2-ve) intratelencephalic-projection neurons (IT-PNs) from layer 5 of the motor cortex. Comparatively, each IT-PN type has a distinct electrophysiological phenotype and the Fezf2+ve IT-PNs display a unique apical dendritic tuft. Here, we aimed to expand our understanding of the molecular underpinnings defining these unique IT-PN types. Using a validated Fezf2-GFP reporter mouse, retrograde labelling techniques and fluorescence activated cell sorting (FACS), combined with a novel approach for low-input RNA-sequencing, we isolated mature Fezf2+ve and Fezf2-ve IT-PNs for transcriptome profiling. Through the comparison of Fezf2+ve and Fezf2-ve IT-PN gene expression profiles, we identified significant enrichment of 81 genes in the Fezf2+ve IT-PNs and 119 genes in the Fezf2-ve IT-PNs. Term enrichment analysis of these enriched genes demonstrated significant overrepresentation of the calcium-binding EF-hand domain in Fezf2+ve IT-PNs, suggesting a greater importance for calcium handling in these neurons. Of the Fezf2-ve IT-PN enriched genes an unexpected and unique enrichment of genes, previously associated with microglia were identified. Our dataset identifies the molecular profiles of two unique IT-PN types in the mature M1, providing important targets to investigate for their maintenance in the healthy mature brain.